2014
DOI: 10.1016/j.str.2014.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Insights into the Recruitment of Talin by RIAM in Integrin Signaling

Abstract: Plasma membrane (PM)-bound GTPase Rap1 recruits the Rap1-interacting-adaptor-molecule (RIAM), which in turn recruits talin to bind and activate integrins. However, it is unclear how RIAM recruits talin and why its close homolog lamellipodin does not. Here we report that, although RIAM possesses two talin-binding sites (TBS1 and TBS2), only TBS1 is capable of recruiting cytoplasmic talin to the PM, and the R8 domain is the strongest binding site in talin. Crystal structure of an R7R8:TBS1 complex reveals an une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 47 publications
(85 reference statements)
3
80
0
Order By: Relevance
“…Known activators include the phosphoinositide PIP2 (Martel et al, 2001), as well as the Rap1 effector RIAM and the heterotrimeric G protein Gα13, both of which bind F3 and displace R9 (Yang et al, 2014;Schiemer et al, 2016), and Kank2, which binds R7 to activate talin (Sun et al, 2016). Both RIAM and PIP2 also contribute to talin activation by bringing it to the membrane Goult et al, 2010;Chang et al, 2014).…”
Section: Regulation Of Talin Interactionsmentioning
confidence: 99%
“…Known activators include the phosphoinositide PIP2 (Martel et al, 2001), as well as the Rap1 effector RIAM and the heterotrimeric G protein Gα13, both of which bind F3 and displace R9 (Yang et al, 2014;Schiemer et al, 2016), and Kank2, which binds R7 to activate talin (Sun et al, 2016). Both RIAM and PIP2 also contribute to talin activation by bringing it to the membrane Goult et al, 2010;Chang et al, 2014).…”
Section: Regulation Of Talin Interactionsmentioning
confidence: 99%
“…This interaction was identified by coimmunoprecipitation using lysates of Chinese hamster ovary (CHO) cells stably expressing integrin a IIb b 3 and transiently cotransfected with hemagglutinin (HA)-tagged talin and various GFP-tagged human RIAM constructs of different lengths (26). Subsequently, it was discovered that the N-terminal domain of RIAM has two distinct TB sites (TBS1 and TBS2), but only TBS1 can recruit talin to the plasma membrane (27). RIAM TBS1 and TBS2 can recognize multiple sites in talin-R (rod) and talin-H (head) F2F3 regions, suggesting that multiple RIAM molecules bind to a single talin molecule.…”
Section: Interaction With Talinmentioning
confidence: 99%
“…However, TBS1, but not TBS2, interacts with talin in the cytoplasm, and the R8 domain of talin, which forms hydrophobic and electrostatic interactions with RIAM, is the strongest binding site for the TBS1 region of RIAM. The interaction of RIAM TBS1 with talin R8 is responsible for recruiting talin to the plasma membrane (27). Furthermore, RIAM TBS1 binds to talin-H region at the F3 subdomain, located in close proximity to the integrin-binding site, which is also located in the F3 subdomain of talin (28).…”
Section: Riam Is An Integral Part Of the Integrin Activation Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the small G protein Rap1 (which has two isoforms, Rap1a and Rap1b) is involved in this unmasking process (Han et al, 2006). Upon activation by protein kinase C, Rap1 is localized to the plasma membrane and recruits its effector molecule, Rap1-GTP-interacting adaptor molecule (RIAM, also known as APBB1IP) (Han et al, 2006;Wynne et al, 2012), which binds to talin to reveal the integrin-binding site (Chang et al, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%